Leukotriene C4-Synthesis Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
A leukotriene C4-synthesis deficiency, a new inborn error of eicosanoid metabolism characterized by hypotonia, microcephaly, failure to thrive, and retarded development, is described in an infant who died aged 6 months after a rapidly progressive course at the University of Heidelberg, Germany.